Striving for autonomy in everyday diabetes self-management—qualitative exploration via grounded theory approach - Viola Sallay; Andrea Klinovszky; Sára Imola Csuka; Norbert Buzás; Orsolya Papp-Zipernovszky (BMJ Open)
Objectives The rapid worldwide increase in the incidence of diabetes significantly influences the lives of individuals, families and communities. Diabetes self-management requires personal autonomy and the presence of a supportive social environment. These attributes can considerably ameliorate the outcomes of the chronic condition. However, little is known about individual variations in overcoming the illness-related challenges and in the achievement of autonomy in daily activities. This paper seeks to bridge this knowledge gap.Design This qualitative study used the grounded theory approach. Semi-structured interviews were conducted, and the data collection and data analysis probed participant experiences of autonomy through the self-management of their daily socio-physical environments.Setting Participants were recruited from the outpatient ward of a university clinic in Hungary.Participants The study was conducted with 26 adult patients with type 2 diabetes mellitus (15 females and 11 males aged between 26 and 80 years; M=62.6 years; SD=13.1). The inclusion criteria were: T2D diagnosis at least 1 year before the beginning of the study; prescribed insulin injection therapy; aged over 18 years; native Hungarian speaker and not diagnosed with dementia or any form of cognitive impairment.Results The study established three principal aspects of the active construction of personal autonomy in diabetes self-management: coping strategies vis-à-vis threats posed by the symptoms and the treatment of the disease; autonomous ways of creating protective space and time and relationship processes that support everyday experiences of self-directedness.Conclusions The results of this study confirm the validity of the self-determination theory in diabetes self-management. They also imply that pathways towards constructing everyday experiences of self-directedness in participants lead through self-acceptance, supporting family relationships and a doctor–patient relationship characterised by partnership. The tentative empirical model of pathways towards patients’ experience of self-directedness can serve as a framework for future research, patient-centred clinical practice, and education.